Generation and characterization of monoclonal antibodies against mature hepcidin and its application to neutralization and quantitative alteration assay. Issue 2 (20th January 2021) - Sakamoto, Shinji; Kirinashizawa, Mika; Mohara, Yumi; Watanabe, Yoshihiro
ABSTRACT: Hepcidin regulates the quantity of ferroportin (FPN) on cellular membrane. In our cell assay expressing ferroportin labeled with green fluorescence, FPN was internalized and degraded only after treatment with hepcidin-25, not hepcidin-22 or hepcidin-20, leading to accumulation of cellular iron. Thus we generated murine monoclonal antibodies (mAbs) against hepcidin-25, and then characterized and validated their functions. Among them, several mAbs showed a neutralizing activity that may prevent ferroportin internalization induced by hepcidin-25. To measure hepcidin level in various fluids, mAbs specific for human and rat hepcidin-25 were selected. As for rat, a sandwich ELISA developed using clone rHN1 as capture antibody and biotinylated clone mHW1 as a detection reagent had high sensitivity, allowing for the detection of 1-100 ng/mL of hepcidin-25. Rat hepcidin-25 level in plasma was measured at an average concentration of 63.0 ng/mL in healthy condition, and at 218.2 ng/mL after stimulation of lipopolysaccharide. Graphical Abstract: